Applications for a-Si:H TFTs: Modelling and Simulation - Lourenço, Paulo (2020)
Hydrogenated amorphous silicon thin film transistors have been used as switching elements in liquid crystal displays and large area matrix addressed sensor arrays. Later, these devices have also been used as analogue active elements in organic light emitting diode displays. However, this technology suffers from bias induced meta-stability. This issue introduces both threshold voltage and subthreshold slope shifts over time when gate bias is applied. Such instabilities jeopardize long term performance of circuits that rely on these components. Nevertheless, hydrogenated amorphous silicon thin film transistors present an exponential transfer characteristic when operating on subthreshold region and their typical power consumption is under 1 µW. This low power characteristic makes these devices ideally suited for low power electronic design.This work demonstrates, through transient analysis of a well-established simulation model for hydrogenated amorphous silicon, the viability of thin film transistors technology to perform both analogue and digital functions. Hence, these structures may be used in both application fields. To this end, two different sets of analyses have been conducted with hydrogenated amorphous silicon based thin film transistors. The first set considers a driving circuit for an active matrix of organic light emitting diodes, biased in a way to minimize the “memory effect” (increasing shift on threshold voltage) due to long term operation. The second set of analyses were conducted upon the implementation of complementary output universal gates, namely NOR/OR and XNOR/XOR elements.